The characteristic damage of analytic theology: a response to William Wood - Yadav, Sameer (Religious studies, 2025)
In Analytic Theology and the Academic Study of Religion William Wood argues that the discipline of analytic theology (AT) can make a distinctively valuable contribution to the mainstream academic study of religion. He deftly navigates the intellectual public relations work required to secure mutual appreciation across these domains of scholarly discourse. In evaluating the characteristic goods of AT, Wood also seeks to recognize and address what Laruen Winner calls ‘characteristic damage’ or deformation in the practice of AT, which he identifies with its apparent inadequacies in addressing ‘history, mystery, and practice’ in the study of religion and theology. I argue that Wood's diagnosis fails to recognize how AT's characteristic damage emerges from its monomaniacal fixation on the epistemic value of theological theorizing to the exclusion of disciplined attention to other kinds of value. While at one point he engages a previously published version of this critique (as an explanation for AT's neglect of liberation theology), he mischaracterizes my argument in that paper in ways that lead him to miss its relevance to the objections from history, mystery, and practice. These objections can be met, I suggest, but only by significant reform to AT as currently practised.